2021
DOI: 10.1002/er.7135
|View full text |Cite
|
Sign up to set email alerts
|

Insight into structural and electrochemical properties of Mg‐doped LiMnPO 4 /C cathode materials with first‐principles calculation and experimental verification

Abstract: The LiMnPO 4 material has the advantages of abundant raw materials, safety and environmental protection, low price, high theoretical capacity, high stable working voltage platform and so on, showing great potential in lithium-ion batteries. Dissimilar metal ion doping can essentially improve the electronic conductivity of LiMnPO 4 and the material's charge and discharge performance, which is an ideal method to improve the electrochemical performance of LiMnPO 4 . In this paper, the optimal doping concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…In recent years, there are a variety of evidence to prove that the first-principles computing has a critical guiding significance for settling various kinds of problems in the practical application of lithium-ion batteries, such as safety, electronic conductivity, kinetics of lithium-ion embedment, etc. [46][47][48] Thereupon, firstly, we studied the influence of crystal structure, chemical bond composition, electronic structure caused by doping on the electrochemical properties of the materials by first-principles. Plus, LiMn 1-x Fe x PO 4 (x = 0, 1/16, 1/12, 1/8, 1/4) was synthesized by hydrothermal method.…”
mentioning
confidence: 99%
“…In recent years, there are a variety of evidence to prove that the first-principles computing has a critical guiding significance for settling various kinds of problems in the practical application of lithium-ion batteries, such as safety, electronic conductivity, kinetics of lithium-ion embedment, etc. [46][47][48] Thereupon, firstly, we studied the influence of crystal structure, chemical bond composition, electronic structure caused by doping on the electrochemical properties of the materials by first-principles. Plus, LiMn 1-x Fe x PO 4 (x = 0, 1/16, 1/12, 1/8, 1/4) was synthesized by hydrothermal method.…”
mentioning
confidence: 99%
“…However, different electronic structure calculation models can lead to significant discrepancies in results. For instance, using the generalized gradient approximation (GGA) method, Bi et al [35] calculated the bandgap of LiMnPO 4 to be 2.543 eV, while Chang et al [44] and our group [41] calculated it to be 2.532 and 2.15 eV, respectively. When Sgroi et al [45] introduced a correction value (U = 4.5 eV) to the GGA, the obtained bandgap was 3.9 eV, which is close to the 3.8 eV calculated by Zhou et al [16] with GGA þ U.…”
Section: Electronic Conductivitymentioning
confidence: 97%
“…Presently, research on LiMnPO 4 materials using first-principles calculations is primarily concentrated on aspects such as electronic conductivity, [35][36][37] lithium-ion diffusion, [38,39] stability, [40][41][42] and working voltage. [43,44]…”
Section: Applications Of First-principles Calculations In Analyzing T...mentioning
confidence: 99%
“…Fortunately, the force between Mn and O is stronger in the lattice of manganesebased phosphate cathodes (LiMnPO 4 ), featuring highly strong Mn−O binding energy. 21,22 In other words, Mn 2+ can hardly escape from the bondage of the Mn−O bond in that it is difficult for hydrogen atoms of the organic solvent in the electrolyte to interact with oxygen atoms of the active material. 23−26 Therefore, manganese-based phosphate cathodes have high structural stability in the charging−discharging process.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the commercialized LiCoO 2 and LiFePO 4 materials, manganese-based cathodes can be regarded as an ideal choice for the next generation of lithium-ion power battery cathodes because of their abundant reserves, low price, high operating voltage, wide operating temperature range, and nontoxic advantages. Numerous studies have reported that manganese-based oxide cathodes are prone to structural transformation and larger crystal cell volume change during charging–discharging process due to the synergistic Jahn–Teller distortion effect, which will result in lattice oxygen loss and structural migration, greatly hindering the development of their commercial application. Fortunately, the force between Mn and O is stronger in the lattice of manganese-based phosphate cathodes (LiMnPO 4 ), featuring highly strong Mn–O binding energy. , In other words, Mn 2+ can hardly escape from the bondage of the Mn–O bond in that it is difficult for hydrogen atoms of the organic solvent in the electrolyte to interact with oxygen atoms of the active material. Therefore, manganese-based phosphate cathodes have high structural stability in the charging–discharging process.…”
Section: Introductionmentioning
confidence: 99%